(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Salinity is one of the most important abiotic stresses that adversely affects plant growth and development around the world. In order to elucidate the growth and physiological responses of maize genotypes under the first phase of salt stress (12 dS m-1 for two weeks), we investigated some growth and physiological traits at vegetative stage (28 d old plant) of four maize genotypes, namely indigenous yellow pure line, indigenous yellow, hybrid, and indigenous white. Salt stress significantly reduced shoot height and stem diameter in almost all genotypes. Under salt stress, instantaneous water use efficiency was highly increased in indigenous yellow pure line (285.5%), in contrast it was decreased significantly in hybrid (16.99 %) genotype compared to their respective control. Photosynthesis rate (70−87%), transpiration rate (81−91%), and stomatal conductance (80−92%) were significantly reduced due to salinity in all the tested genotypes. In the younger shoot, total phenolics content increased significantly in the young shoots of hybrid (42.26 %) and indigenous yellow pure line (40.03 %) genotypes under the first phase of salt stress. In contrast, there was no significant influence of salinity on total phenolics content of older shoot fraction in any genotype tested. Apparently, the growth and physiological traits were hampered in the first phase of salt stress in all tested genotypes. However, deposition of soluble phenolics under salt stress was genotype and leaf-region specific. As the most traits studied were highly influenced by the salinity in the first phase of salt-stress among genotypes at vegetative stage, breeders can potentially use these traits further in breeding program for the development of maize genotypes tolerant to the salt-stress at the vegetative stage of growth. J Bangladesh Agril Univ 19(1): 14–21, 2021 https://doi.org/10.5455/JBAU.46043